2018
DOI: 10.21608/eajb.2018.11901
|View full text |Cite
|
Sign up to set email alerts
|

A New List to the Entomofauna Associated with Faba Bean, Vicia faba L. (Fabales: Fabaceae) Grown in El-Kharga Oasis, New Valley Governorate, Egypt.

Abstract: Survey of the insect pests and their natural enemies associated with faba bean was conducted at El-Kharga Oasis, New Valley Governorate (Egypt) during the months of mid-October to April of 2015 and 2017. In total 15614 insects belonging to 7 orders and 16 families were collected and identified. The most abundant orders were Hymenoptera (7 families) and followed by Hemiptera (3 families). The most common pest species were cowpea aphid, Aphis carccivora Koch, leafhoppers, Empoasca sp., and black cutworm, Agrotis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 2 publications
(2 reference statements)
2
7
0
Order By: Relevance
“…On the other hand, four hymenopteran parasitoid species were recorded during the growing season of faba bean among them was Opius nitidulator, and these present results were somewhat consistent with those noticed by El-Samahy [28] Last but not least, insect pollinators play a key role in crop pollination and increasing significantly the production of seeds. The honey bee was the most dominant and abundant pollinator in this popular crop in the current study, and this observation was in the same line with those reported by Mabrouk and Mahbob [19] and Abdel Khalek et al [20].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…On the other hand, four hymenopteran parasitoid species were recorded during the growing season of faba bean among them was Opius nitidulator, and these present results were somewhat consistent with those noticed by El-Samahy [28] Last but not least, insect pollinators play a key role in crop pollination and increasing significantly the production of seeds. The honey bee was the most dominant and abundant pollinator in this popular crop in the current study, and this observation was in the same line with those reported by Mabrouk and Mahbob [19] and Abdel Khalek et al [20].…”
Section: Discussionsupporting
confidence: 93%
“…were noticed. The most dominant predators as noted by Abdel Khalek et al[20] were C. septempunctata, C. undecimpunctata, and Ch. carnea.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…).Last but not least, insect pollinators are playing a key role in crop pollination and increasing signi cantly the production of seeds. Honey bee was the most dominant and abundant pollinator in this popular crop in the current study and this observation was in the same line with those reported by(Mabrouk et al 2017;Abdel Khalek et al 2018).…”
supporting
confidence: 93%
“…Japan was the highest with ( Pesticides are toxic substances or a mixture of substances that are naturally or chemically synthesized. These are widely used for controlling harmful weeds (herbicides), fungi (fungicides), bacteria (bactericides), and insect infestations (insecticides) in the agricultural field [52]. Moreover, these can be used against some disease carriers and pests (e.g., ticks, rodents, mosquitoes, and lice) in the entire ecosystem [22].…”
Section: Pesticides As An Environmental Pollutantmentioning
confidence: 99%